Sistem Pembuktian terhadap Praktik Penimbunan Barang Impor Ilegal oleh Pelaku Usaha - Yuni Priskila Ginting; Axel Imanuel Tania; Cherish Young; Felicia Evelyn; Jennifer Almelia Lim; Kenzie Betha Addison; Suhan Chae; Thalia Jamiana Kuang (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
With increasingly tight market competition, illegal imported goods that should have been destroyed because they failed security checks are hoarded by business actors to seek more profit rather than following the laws and regulations that have been set, thus becoming an unlawful act. There are also illegal imported goods that do not even receive checks, but rather go through a smuggling process across state borders. Because of the smuggling process, these foreign goods cannot be traced by the state, so they do not have official distribution permits in trade, and therefore risk causing financial losses to the state because they do not pay any taxes at all. This incident occurs because the public has minimal legal knowledge and does not even care at all about the main reason for seeking maximum profit. Incidents like this often occur due to minimal supervision from the authorities, as well as a lack of evidence to ensure that the business actor can be said to have committed an unlawful act; the legal process is halted.